Trends in Pain Medicine Liability. Issue 3 (June 2016) - Pollak, Kelly A.; Stephens, Linda S.; Posner, Karen L.; Rathmell, James P.; Fitzgibbon, Dermot R.; Dutton, Richard P.; Michna, Edward; Domino, Karen B.
Abstract : (Abstracted from Anesthesiology, 123:1133–1141, 2015) There has been a movement toward the use of more potent analgesics and interventional and interdisciplinary techniques in the treatment of pain since the 1990s. However, whether malpractice claims have increased is unknown.